PERAN ORANG ARAB DALAM SEJARAH PERKEMBANGAN AGAMA ISLAM DI INDONESIA - Anisah, Nia; Maryamah, Maryamah; Purnama, Lidia; Liza, Levi Lauren; Khoirunnisa, Nabila (Jurnal Multidisipliner Bharasumba, 2023)
Factors in this process was the role of the Arabs. Arabs played a significant role in bringing and developing Islam in the Indonesian archipelago. This article using the literature study method will discuss the role of Arabs in the history of the development of Islam in Indonesia. Arabs first came to Indonesia through maritime trade routes that connected the Middle East with Southeast Asia. Arabs who settled in Indonesia helped expand the trade network and became the center of the spread of Islam to the indigenous people. education also played an important role in the spread of Islam in Indonesia by Arabs. They opened madrassas or religious schools in various regions, where locals could learn about the teachings of Islam. In conclusion, the role of Arabs in the spread of Islam in Indonesia was very important. Through trade and education, they brought the teachings of Islam to the Indonesian islands and contributed to the formation of a strong Muslim society in this region.